The importance of partnerships in supply chains - Kmetec, Anja (Array, 2019)
The article deals with an overview of various theories and studies examining the concepts of partnerships, relationships and strategic alliances. We present various perspectives and theories dealing with these concepts, in connection and interdependence with the supply chain and the supply chain management. In conclusion, we try to establish a model to become the basis for our further study of strategic alliances and their strengths.